2020
DOI: 10.1038/s41598-020-69316-0
|View full text |Cite
|
Sign up to set email alerts
|

One Health promotion and the politics of dog management in remote, northern Australian communities

Abstract: Community perspectives are rarely sought or integrated into dog management policy and practice. Dog management in remote communities in Australia has focused on reducing the number of dogs, which is often implemented by visiting veterinarians, despite widely-held opinions that fly-in-fly-out services provide only temporary solutions. We conducted participatory research in a group of remote communities in northern Australia to explore how dog-related problems arise and are managed, and explain their impacts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Such models can be used as decision-support systems, for example, to determine how to best use vaccination, should an incursion occur [ 91 , 92 ]. The output from models creates an opportunity to engage local communities in the process of designing preparedness policy that considers community values [ 93 ], such as how domestic dogs are managed versus how a disease outbreak response might be operationalized [ 94 ••, 95 ]. This recent research in northern Australia has contributed significantly towards the cycle of preparedness planning and response [ 96 ].…”
Section: Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Such models can be used as decision-support systems, for example, to determine how to best use vaccination, should an incursion occur [ 91 , 92 ]. The output from models creates an opportunity to engage local communities in the process of designing preparedness policy that considers community values [ 93 ], such as how domestic dogs are managed versus how a disease outbreak response might be operationalized [ 94 ••, 95 ]. This recent research in northern Australia has contributed significantly towards the cycle of preparedness planning and response [ 96 ].…”
Section: Australiamentioning
confidence: 99%
“…While such programs, driven particularly with foreign assistance, offer the potential for major impact, they are not sustainable without local support. Focusing primarily upon recent literature from the past 5 years [ 1 – 5 , 6 •, 7 14 , 15 •, 16 24 , 25 •, 26 30 , 31 •, 32 •, 33 •, 34 – 51 , 52 •, 53 , 54 •, 55 – 62 , 63 ••, 64 – 66 , 67 •, 68 , 69 ••, 70 – 83 , 84 •, 85 , 86 •, 87 •, 88 ••, 89 , 90 •, 91 93 , 94 ••, 95 100 ], the objective of this communication is to provide an update on rabies in the tropics (narrowly defined as those geographic regions between the Tropic of Cancer and the Tropic of Capricorn) and progress in human and animal case reduction towards the goal of “Zero by Thirty” (ZBT).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In a study in remote Australia, the community members' perceptions about dog conflicts were documented, and the researchers found that they were not as interested in how many dogs there were. Rather, community members sought a balance between the services that the FRDs provided to their community (i.e., protection) and the negative public health effects, including bites and attacks on humans, zoonoses, and poor community hygiene due to dog feces and garbage [48]. This highlights the importance of preliminary consultation with the public to elucidate the problems and then select appropriate solutions based on the local need.…”
Section: Ptrac Designmentioning
confidence: 99%
“…In fact, in a study in remote Australia, it was found that survey respondents were loath to confront their neighbors or call the enforcement department regarding dog-related complaints, and instead chose a "weary acceptance and passive resentment" that tended to create underlying social tensions in the neighborhood [48]. In the case of the Chilean government, they seem to rely on this passive type of enforcement, or in other words, relying on community members to report observed infractions to the authorities, rather than having enforcement officers actively patrolling neighborhoods and delivering fines to offenders.…”
Section: Identification and Registrationmentioning
confidence: 99%
“…The major component of municipal solid waste (MSW) is organic biodegradable waste (70%) that serves as a source of food to free-roaming dogs, thereby attracting these dogs in the densely populated urban slums [33]. The hunger stricken dogs compete for food, and associated aggression among these dogs also endangers local inhabitants and significantly increases the threat of rabies transmission to humans [34]. Proper management of waste in the streets is essential as part of a holistic strategy to minimize free-roaming dog populations as an animal welfare consideration and in support of rabies control [35].…”
Section: Urbanization and Solid Waste And Their Relation To Dog Population Growthmentioning
confidence: 99%